Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) mortality by different Beauveria bassiana (Bals.) Vuillemin strains under laboratory conditions. - Muñoz, José A.; De la Rosa, William; Toledo, Jorge (Instituto de Ecología, A.C., 2009)
Under laboratory conditions of 27 ± 2 °C, 80 ± 5% R. H. and 12:12 L:D, we performed a characterization of 16 strains of the entomopathogenic fungus Beauveria bassiana (Bals.) Vuillemin, through bioessays by immersion. The strains were isolated from different hosts and their pathogenicity was evaluated on Ceratitis capitata (Wiedemann) females. Results showed that mortality of flies ranged from 9.1 to 91.9%. Average lethal time (LT50) of the most pathogenic strain was 3.8 days; while that the less pathogenic strain took 17.6 days. In a second series of experiments, the strains that registered the highest biological activity were evaluated as mentioned above. These strains showed high levels of mortality, spore production and spore recovery from the infected insects. According with these results, we discuss the potential that five strains of B. bassiana have be tested under field conditions to determinate if can be used in the control of this pest.